2009
DOI: 10.1097/phm.0b013e3181a9f30d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gait Analysis Between Anterior and Posterior Ankle Foot Orthosis in Hemiplegic Patients

Abstract: Wearing anterior ankle foot orthosis was as useful as posterior ankle foot orthosis for correcting hemiplegic gait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 9 publications
8
63
0
Order By: Relevance
“…An ankle-foot orthosis (AFO) can improve the gait of hemiplegic individuals [12,13]; however, the limited ankle motion associated with an AFO with plantarflexion stop [14,15], AFO with bilateral stop [13], or unarticulated AFO [16], seems to be disadvantageous for ankle function, because both heel and forefoot rocker functions require adequate plantarflexion range. An AFO with an oil damper (AFO-OD) was developed to assist the heel rocker function [17,18]; however, differences between an AFO-OD and an AFO with limited motion are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…An ankle-foot orthosis (AFO) can improve the gait of hemiplegic individuals [12,13]; however, the limited ankle motion associated with an AFO with plantarflexion stop [14,15], AFO with bilateral stop [13], or unarticulated AFO [16], seems to be disadvantageous for ankle function, because both heel and forefoot rocker functions require adequate plantarflexion range. An AFO with an oil damper (AFO-OD) was developed to assist the heel rocker function [17,18]; however, differences between an AFO-OD and an AFO with limited motion are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Wong et al 13 and Park et al 10 observed no significant difference between the A-AFO and P-AFO in increasing walking speed, stride strength, and velocity. Sheffler et al 34 found that stroke patients with the P-AFOs improved significantly (relative to no device) in the floor, the carpet, and the Bup and go[ tasks and a trend toward significantly in the obstacle and stair tasks of mEFAP.…”
Section: Discussionmentioning
confidence: 94%
“…4Y8 Because of hot weather, people in some Asian countries used to walk with bare feet indoors, and P-AFO is not suitable under such conditions. 9,10 In Taiwan, a low-temperature customized molded plastic anterior AFO (A-AFO) ( Fig. 1), which could be worn barefoot indoors as well as with shoes, is the principal orthotic intervention for residual ankle weakness poststroke.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Anterior and posterior AFOs were compared in persons with hemiplegia, and the BBS scores did not differ significantly for any condition (barefoot, anterior AFO, or posterior AFO), although gait measures did differ significantly between the barefoot and AFO conditions. 16 It is also important to note that the average BBS in this study was 37.3, meaning that the average subject was at the upper end of the medium fall risk category. Simons et al 17 found that AFOs did significantly improve BBS score, when compared with no AFO, in stroke survivors.…”
Section: Clinical Measures Of Balance For Adults With Locomotor Disormentioning
confidence: 98%